Status report on Indonesian galliformes - Derek A Holmes (KUKILA, 1989)
This is a preliminary report on the status of galliformes in Indonesia, which has been prepared with three objectives: to alert conservationists to areas of danger, to demonstrate the paucity of data for most species, and to serve as a basis for updating Information. An IUCN/ICBP Red Data Book' category is given for each species (endangered, vulnerable, rare, Indeterminate and out of danger), but it cannot be too strongly emphasized that this category, which refers only to Indonesia, is PROVISIONAL; in many cases it 1s little more than a guess. Against each species is also stated whether or not -it is protected under Indonesian law.